2019
DOI: 10.1302/0301-620x.101b1.bjj-2018-0874.r1
|View full text |Cite
|
Sign up to set email alerts
|

Does having a rotator cuff repair prior to reverse total shoulder arthroplasty influence the outcome?

Abstract: Aims The number of rotator cuff repairs that are undertaken is increasing. Reverse shoulder arthroplasty (RSA) is the procedure of choice for patients with rotator cuff arthropathy. We sought to determine whether patients who underwent rotator cuff repair and subsequent RSA had different outcomes compared with a matched control group who underwent RSA without a previous rotator cuff repair. Patients and Methods All patients with a history of rotator cuff repair who underwent RSA between 2000 and 2015 with a mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 18 publications
0
41
0
Order By: Relevance
“…Patients with a previous RCR have been shown to derive benefit from RTSA [39]. However, there is no consensus on whether a history of RCT is an independent risk factor for inferior RTSA outcomes [39][40][41][42][43].…”
Section: Rtsa For Massive Irreparable Rotator Cuff Tearsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with a previous RCR have been shown to derive benefit from RTSA [39]. However, there is no consensus on whether a history of RCT is an independent risk factor for inferior RTSA outcomes [39][40][41][42][43].…”
Section: Rtsa For Massive Irreparable Rotator Cuff Tearsmentioning
confidence: 99%
“…However, when looking specifically at a patient's history of undergoing a previous RCR, the evidence has shown conflicting results in short-term follow-up studies. The number of RTSAs performed after a failed RCR has been steadily increasing, but it has yet to be established if a previous RCR to the ipsilateral shoulder leads to inferior outcomes [41,43].…”
Section: Prior Surgerymentioning
confidence: 99%
“…A growing amount of literature continues to support the use of RTSA to treat patients who have previously undergone RCR with persistent pain and shoulder dysfunction. 13,26 Erickson et al 13 recently reported significant improvements in patientreported outcome measures at 2 years after RTSA in patients who had previously undergone RCR and concluded that a previous RCR does not appear to adversely affect the early outcome after RTSA. Therefore, when faced with a patient who has Medicare and whose RCR has clinically failed, it is likely becoming increasingly common to perform an RTSA compared with a revision RCR and thus important to study as an endpoint when examining RCR outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Although most patients who have undergone RTSA have had good clinical results, some have had poor outcomes and high rates of complications, reoperations, and revisions [11,12]. These poor outcomes were dependent on several factors including age, gender, previous rotator cuff repair surgery, and preoperative functional scores such as the American Shoulder and Elbow Surgeons (ASES) score [11,[13][14][15][16]. Additionally, surgeons are able to predict patient outcomes of RTSA based on the preoperative stage of the disease [17].…”
Section: Introductionmentioning
confidence: 99%